Death, quest, and self-esteem: re-examining the role of self-esteem and religion following mortality salience - Arrowood, Robert B. (Religion, brain & behavior, 2018)
Terror management theory suggests that when mortality concerns are salient, religion can serve as a defence in order to boost self-esteem and shield against the potential for anxiety. The current study examined whether individual differences in religious orientation (i.e., quest) interacted with reminders of death to influence well-being. To the extent that religiosity buffers against mortality awareness on defensiveness, the present results demonstrated that individuals high in quest orientation, in comparison to low-quest-orientated individuals, reported lower well-being (i.e., self-esteem) following reminders of death. These results add to the existing body of literature suggesting that thoughts of death can serve to decrease well-being, but that this effect is influenced by individual differences, namely trait quest religiosity.